2004
DOI: 10.1038/nature02468
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular gate opening in Shaker K+ channels defined by high-affinity metal bridges

Abstract: Voltage-gated potassium channels such as Shaker help to control electrical signalling in neurons by regulating the passage of K+ across cell membranes. Ion flow is controlled by a voltage-dependent gate at the intracellular side of the pore, formed by the crossing of four alpha-helices--the inner-pore helices. The prevailing model of gating is based on a comparison of the crystal structures of two bacterial channels--KcsA in a closed state and MthK in an open state--and proposes a hinge motion at a conserved g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
206
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(238 citation statements)
references
References 28 publications
29
206
2
1
Order By: Relevance
“…In contrast to these results, trapping experiments by avidin of site-specific biotinylated channels with the bacterial KvAP channel have suggested a rather large translation of the S4 segment across the membrane (8,19). The crystal structure of Kv1.2, a eukaryotic potassium channel recently solved (20), is thought to represent the open (inactivated) state based on previously reported biochemical and electrophysiological studies (9,12,27,35). However, despite the accumulating experimental data, the structural constraints providing information about the closed state conformation of the voltage sensor remain scarce and uncertain.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…In contrast to these results, trapping experiments by avidin of site-specific biotinylated channels with the bacterial KvAP channel have suggested a rather large translation of the S4 segment across the membrane (8,19). The crystal structure of Kv1.2, a eukaryotic potassium channel recently solved (20), is thought to represent the open (inactivated) state based on previously reported biochemical and electrophysiological studies (9,12,27,35). However, despite the accumulating experimental data, the structural constraints providing information about the closed state conformation of the voltage sensor remain scarce and uncertain.…”
mentioning
confidence: 73%
“…Assumption 2. The intracellular gate is constructed according to the data of the Yellen laboratory (24)(25)(26)(27), which shows that cysteine side chains in the Shaker mutant V478C remain accessible to a series of fairly large reagents and that a high-affinity Cd 2ϩ binding site can be reached in the closed state. The closed gate formed by straight ␣-helices as observed in the x-ray structure of the KcsA channel is not compatible with these observations because the corresponding position is located deep within the narrow helical bundle crossing and would not be accessible from the intracellular side by large reagents or by Cd 2ϩ .…”
Section: Discussionmentioning
confidence: 99%
“…In the Shaker channel, it has been suggested that opening of the gate is expected to be accomplished by swiveling the lower half of the S6 below the PXP motif (32,40), with only modest changes in dimension at the position of V474C within the Shaker PVP motif (23,32). Although gating shifts reported for V474 mutation may somewhat contradict the idea that V474 changes little during gating (34,35), it is the case that Shaker S6 positions with the strongest energetic effects on gating extend largely from V474 down to perhaps N482.…”
Section: Discussionmentioning
confidence: 99%
“…In Shaker channels, Cd 2+ irreversibly inhibits two S6 cysteine mutants (I470C and V474C, corresponding to F315C and V319C in BK, respectively, based on linear alignment) by forming strong coordination with three or four cysteines individually introduced at these pore lining sites (23). This coordination by Cd 2+ defines a diameter in Shaker of approximately 8 to 9 Å separating diagonal cysteines (32). In BK channels, however, we observed no irreversible inhibition produced by Cd 2+ treatment at any of the S6-substituted cysteine mutants.…”
Section: Mtset Modification At the Single Channel Level Defines A Lowmentioning
confidence: 99%
“…Despite the position of this proline residue, these channels are activated by depolarization. Moreover, this proline residue is thought to provide an essential bend in the S6 helix that is important for K V channel gating (26). It will be interesting to determine whether substitution of other amino acid residues at this position in K V channels can produce hyperpolarizationactivated gating.…”
Section: Bending Of S6 Segments Determines Both Voltage Dependence Andmentioning
confidence: 99%